The radiative forcing variability caused by the changes of the upper cloud vertical structure in the Venus mesosphere. (August 2015) - Lee, Y.J.; Titov, D.V.; Ignatiev, N.I.; Tellmann, S.; Pätzold, M.; Piccioni, G.
Abstract: The upper cloud layer of Venus is a key factor affecting radiative energy balance of the mesosphere. Observations of the temperature and the cloud top structure by Venus Express revealed their strong variability with latitude. We used the 1-D radiative transfer model to study the dependence of the radiative forcing on the cloud top structure. The cloud top altitude effectively controls outgoing thermal fluxes. Sharp cloud top boundary can produce a pronounced peak of both solar heating and thermal cooling that suggests a radiative origin of temperature inversions in the cold collar. Strong diurnal variation of net forcing at low latitudes can be responsible for the origin of convective cells observed in UV images. Latitudinal contrasts in the radiative forcing in the mesosphere can drive meridional Hadley-type circulation with meridional winds of few m/s and vertical motions with speed of few cm/s. Abstract : Highlights: We studied radiative forcing variations due to clouds of the Venus mesosphere. The atmospheric model is derived from the Venus Express observations. The cloud top structure affects cooling and heating rates significantly. Strong diurnal variation of net forcing at the cloud top level is expected. Meridional net forcing unbalance requires a Hadley-like circulation in the mesosphere.